1997
DOI: 10.1007/s004490050402
|View full text |Cite
|
Sign up to set email alerts
|

Prickly pear cladodes and fruits as a potential raw material for the bioindustries

Abstract: The biomass of prickly pear cladodes and fruits are a potential raw material for fermentations and are of particular consideration for arid and semi-arid regions, where its cultivation would also make use of an important land areas. This paper reviews the attempts of uses of prickly pear cladodes and fruits in food and biotechnological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…[5,[7][8][9] The utilization of the cactus pear has been focused around the edible part of the plant (cladodes and fruit pulp). The fruit is rich in amino acids, sugars, vitamins and minerals while both the fruit and cladodes have antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,[7][8][9] The utilization of the cactus pear has been focused around the edible part of the plant (cladodes and fruit pulp). The fruit is rich in amino acids, sugars, vitamins and minerals while both the fruit and cladodes have antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…The development of methods to utilize these by-products of seeds are important. [7,14,19,20,21] Seed oil of cactus pear are exceptionally valuable because of its high content in the parent of the omega-6 essential fatty acid family (linoleic acid), vitamin E (1000 mg kg À1 ), and sterols (10 g kg À1 ). [17] Previous research has shown distinct characteristics of these oils, such as a high level of unsaturation (82%), consisting of the principal linoleic (65.43%), and oleic (15.04%) acids.…”
Section: Introductionmentioning
confidence: 99%
“…The cladodes, also known as cactus pads, of the spineless cultivars can be used as livestock feed, but because of their low crude protein content of about 40 g kg −1 they should be regarded as a cheap energy source rather than as a balanced fodder crop . For instance, a ration for non‐reproductive sheep should contain at least 70 g crude protein kg −1 ; this necessitates the supplementation of cactus cladodes with some form of crude protein for use as a balanced animal feed . Because of the high annual productivity of 10–40 tonnes (dry weight) of cladode biomass per hectare, the cladodes have potential as a lignocellulosic feedstock to produce a protein‐enriched biomass product for use as an animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…The nutritional value of nopalitos is considered to be intermediate between that of lettuce and spinach [1]. In addition, nopalitos are used to prevent scurvy and to alleviate diabetes [2]. Also, nopalitos are high in dietary fibre (18-82% dry matter basis; db); they show intermediate levels of b-carotene (provitamin A; 260 lg/100 g db) and contain calcium, potassium, phosphorus, and sodium [3].…”
Section: Introductionmentioning
confidence: 99%